The effect of fermentation time on bioethanol levels from sugar cane (saccharum officinarum) - Rizaldi, Lalu Heri; -, Mikratunnisa; Rinjani, Fitrina Utari; Amrullah, Shafwan (Jurnal Agrotek Ummat, 2022)
High energy consumption has an impact on the crisis caused by the decline in fossil energy reserves, so that Indonesia must have other energy alternatives in the form of biofuels, namely bioethanol. Knowing the effect of fermentation time on ethanol content, pH value, and brix content obtained from sugarcane juice is the purpose of this study. Using completely randomized design (CRD) with fermentation time factor. Research shows that fermentation time has an effect on ethanol content and acidity (pH), but has no effect on sugar content (brix). The best treatment was obtained at 6 days of fermentation with ethanol content of 7.67%, acidity (pH) 4.87%, and sugar content (brix) 6.33%. the ratio of high and low amount of ethanol produced is influenced by sugar consumption and yeast growth during the fermentation process.